Reading personal photographs: a case study at an Israeli art college on multiple identities. Issue 1 (3rd April 2019) - Heruti, Vered
Abstract: This article presents a pedagogical–visual process developed in a traditional frontal-format course with a multi-identity group of students set in a large lecture hall. It examines an assignment that required students to analyze a meaningful personal photograph and connate it culturally, while internalizing visual general patterns utilizing a sharing digital forum. This activity promotes combining visual theories with relevant introspective self-expression, emphasizing multi-identities. One can relate this utilization of visual tools to Paulo Freire's approach to dialogic pedagogy, which emphasizes the relevance to learners and the shift between the personal and the cultural, helping to confront the heterogeneity of the class.